The Students’ Interest in Learning English Through Teacher’s Strategies in Eleventh Grade at SMK Negeri Sulbar - T, Muhammad Ybnu; Aras, Muhammad Sahrir (Jurnal Ilmiah Multidisiplin Amsir, 2023)
This research is qualitative descriptive research. The instruments of the research are interviews, observation, and documentation. The population of the research is the students of class XI SMK Negeri SULBAR, and the sample of the research is students of class XI ATP (Plantation Agribusiness) as many as 18 students. The research was conducted from March to April 2023. The objectives of the research are to explore what kind of strategies are used by the teacher in teaching in the classroom, and the effective strategy used by the teacher in teaching in the classroom.